2005
DOI: 10.1016/j.lisr.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective on library association codes of ethics

Abstract: This study of 28 countries involves comparative content analysis of the English versions of codes of ethics proposed by professional associations. It yielded an empirically grounded typology of principles arranged in twenty categories. The most frequently identified principles were professional development, integrity, confidentiality or privacy, and free and equal access to information. While confidentiality and privacy, and equal access to information, appear in all existing typologies of library and informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 20 publications
1
40
0
1
Order By: Relevance
“…When Dole and Hurych [12] asked library science students at one university to rank the three most important values of the profession, 89% of students included "service to clientele" and 32% included "equitable access" in this top tier. Free and equal access is a core ethical principle that is found in all library ethical values typologies [e.g., 16,22,18,25,33,34,37]. Shachaf [34] found that equal access was one of the few core values of the library profession that was shared across 23 countries around the globe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Dole and Hurych [12] asked library science students at one university to rank the three most important values of the profession, 89% of students included "service to clientele" and 32% included "equitable access" in this top tier. Free and equal access is a core ethical principle that is found in all library ethical values typologies [e.g., 16,22,18,25,33,34,37]. Shachaf [34] found that equal access was one of the few core values of the library profession that was shared across 23 countries around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Free and equal access is a core ethical principle that is found in all library ethical values typologies [e.g., 16,22,18,25,33,34,37]. Shachaf [34] found that equal access was one of the few core values of the library profession that was shared across 23 countries around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Shachaf conducted a comparative content analysis of the codes of ethics proposed by professional associations in twenty-eight countries and found that professionalism, integrity, confidentiality/privacy, and free and equal access to information were the most frequently noted principles. 6 She explained that there were three key types of codes: aspirational, regulatory, and educational. 7 Barsh and Lisewski believe that the ALA Code is primarily aspirational as it does not regulate or provide concrete guidance on implementing systems of procedures for dealing with ethical dilemmas.…”
Section: For Your Enrichmentmentioning
confidence: 99%
“…Specifically, she determined that 85 percent of the codes of ethics in her study contain privacy protection. 16 The ALA and other professional organizations justify privacy protections by appealing to intellectual freedom. 17 In the ALA's words, intellectual freedom requires that one have the ability to "seek and receive information from all points of view without restriction" and "true freedom of inquiry" does not exist where "users recognize or fear that their privacy or confidentiality is compromised."…”
Section: May 2015mentioning
confidence: 99%